MOTIVATIONS BEHIND LUBUKUSU DIALECT AND ENGLISH CODE SWITCHING DURING COMMUNICATION AMONG SPEAKERS IN BUNGOMA COUNTY, KENYA - Benard W. Wangila,; David Wafula Lwangale, (IJRDO- Journal of Educational Research, 2020)
The effect of globalization, migrations, social interactions and search for identity has led to an increased linguistic phenomenon of language contact hence bilingualism and multilingualism. Besides, language, a rather dynamic concept is not static and has always been subject to political, social and economic changes throughout human history as most speakers of any language or dialect at any given time would resort to code switching and mixing or borrowing whenever they communicate in their local languages or dialects. As a result, it would shape and influence the speech patterns of the speakers. Code switching therefore is defined by Wardwaugh (1998) as shifting as the need arises, from one code to another .Although it may seem as obvious phenomenon, the important thing is not that code switching occurs but the main reasons why people decide to code switch. Furthermore, people are likely to ask questions such as who somebody is, where they are from and what they are in the eyes of the society in which they belong on the basis of the speech they are engaged in. Consequently, as people participate and communicate in different social domains owing to their different social roles, they influence their language of communication and their communicative intent. They do this by code switching and mixing their speech either consciously or otherwise. This aspect of bilingualism where people code switch from one language to another or within the same language, the manner in which they undertake this phenomenon could either be regarded as smooth or ‘uneventful’ in one way or purposeful in some other way. This means that either the speaker or the context of the speech influences code switching and mixing patterns or even the message. It was on that perspective that this study sought to investigate the effect of code switching and mixing of Lubukusu and English on communication among Lubukusu speakers of Bungoma County, Kenya. The general aim of the study was to fill the sociolinguistic gap on how code switching and mixing between a local language and a dominant language would influence communication in certain contexts/ social domains among Lubukusu speakers of Bungoma County as existing literature indicate most studies in this area have majorly dwelt on phonological, morphological and syntactic studies of Lubukusu but little or no study has been undertaken in contact area, especially from the domain perspective .The study’s objective was to find out  motivations behind code switching and mixing among Lubukusu speakers of Bungoma County. The study’s research design was qualitative. Interview schedules and participant observation mode were applied in all aspects of the study. The target population was Lubukusu speakers of varying age groups from Bungoma County. The total respondents were 80 local Lubukusu speakers from Bungoma Central Sub county selected using a purposive sampling method. The researcher collected data using both open ended and structured interview schedules, partly developing some themes from the collected data. The study aims at coming up with findings that would contribute new knowledge on language dynamism that may be relevant to the field of linguistics, sociology and sociolinguistics.